Management of endo-perio lesion in a tooth with an unfavorable prognosis : a clinical case report with an 18-month follow-up = Tratamiento de una lesión endo-perio-perio en un diente de pronóstico desfavorable:informe de un caso clínico con seguimiento durante 18 meses - Sandini Trentin, Micheline
The aim of this case study is to report a successful clinical case of an endo-perio lesion in a tooth with an initially unfavorable prognosis, followed up for 18 months. A male patient, public servant, non-smoker, without a history of diabetes, and married sought dental treatment in 1995 due to periodontal problems. He was then 40 years old and diagnosed with moderate to advanced periodontal disease. The initial treatment consisted of supra and subgingival scaling, followed by the extraction of teeth indicated for removal. After discharge, the patient adhered to a preventive periodic maintenance (PPM) program to control periodontal disease recurrence. In 2021, tooth 43 showed an unfavorable endo-perio lesion during a routine check-up. Despite treatment options, the patient opted for conservative treatment with endodontic and periodontal procedures. Simultaneously, PPM sessions were performed. The patient was monitored every six months, showing regression of periodontal pockets and significant improvement after 18 months. This case highlights the importance of patient adherence to PPM, demonstrating that a conservative approach and proper maintenance can lead to positive clinical outcomes even in cases with an initially unfavorable prognosis.